2002
DOI: 10.1007/s00412-002-0196-2
|View full text |Cite
|
Sign up to set email alerts
|

Ty1/copia- and Ty3/gypsy-like DNA sequences in Helianthus species

Abstract: Two repeated DNA sequences isolated from a partial genomic DNA library of Helianthus annuus, p HaS13 and p HaS211, were shown to represent portions of the int gene of a Ty3 /gypsy retroelement and of the RNase-Hgene of a Ty1 /copia retroelement, respectively. Southern blotting patterns obtained by hybridizing the two probes to BglII- or DraI-digested genomic DNA from different Helianthus species showed p HaS13 and p HaS211 were parts of dispersed repeats at least 8 and 7 kb in length, respectively, that were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 18 publications
3
45
0
Order By: Relevance
“…The fragment of Ty3-gypsy-like retroelements cloned, labeled, and used in FISH produced signals that were scattered throughout the chromosomes and accumulated also in heterochromatic regions, including the cp-rDNA-like/GCrich. The Ty1-copia-and Ty3-gypsy-like retroelements comprise a very common and heterogeneous retroelement group in the plant kingdom (Flavell et al 1992;Todorovska 2007) and, in general, are found dispersed throughout chromosomes (Santini et al 2002) or grouped in specific regions (Belyayev et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The fragment of Ty3-gypsy-like retroelements cloned, labeled, and used in FISH produced signals that were scattered throughout the chromosomes and accumulated also in heterochromatic regions, including the cp-rDNA-like/GCrich. The Ty1-copia-and Ty3-gypsy-like retroelements comprise a very common and heterogeneous retroelement group in the plant kingdom (Flavell et al 1992;Todorovska 2007) and, in general, are found dispersed throughout chromosomes (Santini et al 2002) or grouped in specific regions (Belyayev et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The same could be true for any genome even if the fact that we have its entire DNA sequence gives us the illusion that we know all about it. Although many TE families in Drosophila and plants are found in both euchromatin and heterochromatin, some are preferentially located in heterochromatin, where they can be found in clusters, and others mainly in euchromatin (Dimitri, 1997;Di Franco et al, 1997;Terrinoni et al, 1997;Santini et al, 2002;Alonso-Gonzalez et al, 2003). It is therefore suggested that the higher the fraction of copies of a given element in heterochromatin, the older the invasion of the genome by this TE.…”
Section: Tes In Heterochromatinmentioning
confidence: 99%
“…Besides this general dispersed tendency, both species exhibited a concentration of these elements in some terminal regions, associated with NORs, which are also associated with GC-rich heterochromatin (Fregonezi et al, 2004). Retroelements have previously been reported to be associated with the NORs of some Triticeae (Belyayev et al, 2001), with the heterochromatin of Allium cepa (onion) (Pearce et al, 1996) and A. thaliana , and with centromeric regions in several monocotyledons (Kumar and Bennetzen, 1999) and dicotyledons (Santini et al, 2002). Retrotransposons have also been reported to be associated with the whole genome as segments dispersed along the A-and D-chromosomes of Avena sativa (oat) (Linares et al, 2001).…”
Section: Discussionmentioning
confidence: 77%